2019
DOI: 10.3390/nu11020295
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Glutathione, Garlic Derivatives, and Hydrogen Sulfide

Abstract: Glutathione and aged garlic extract are sulfur-containing products that play important protective and regulatory roles within the immune system and in oxidative processes. Hydrogen sulfide (H2S), an endogenous, gaseous, signaling transmitter, has also been shown to be involved in the regulation of inflammation. Recent studies have shown that sulfur-containing compounds from garlic have beneficial effects in attenuating outcomes associated with cardiovascular disease and inflammation by a mechanism that may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 149 publications
(170 reference statements)
2
67
0
Order By: Relevance
“…H 2 S appears to play an important role in the modulation of the immune response by regulating the post-translational modification of the NF-kB pathway. However, depending on the model and the concentration used, H 2 S functions as an activator and an inhibitor towards this pathway [100]. H 2 S donors also inhibit macrophage pro-inflammatory cytokine production, as well as cyclooxygenase-2 and nitric oxide production, and decrease macrophage motility.…”
Section: Sulfur Compoundsmentioning
confidence: 99%
“…H 2 S appears to play an important role in the modulation of the immune response by regulating the post-translational modification of the NF-kB pathway. However, depending on the model and the concentration used, H 2 S functions as an activator and an inhibitor towards this pathway [100]. H 2 S donors also inhibit macrophage pro-inflammatory cytokine production, as well as cyclooxygenase-2 and nitric oxide production, and decrease macrophage motility.…”
Section: Sulfur Compoundsmentioning
confidence: 99%
“…TOMM20 exhibited a growth from N>P&P>M in the first dataset while in the second dataset there is a total rise from N>M. Except for CBS expression, Our results for H2S producers CSE1L, TOM20 and H2S scavengers (ETHE1, SQOR) are in favor of cancer progression and suggest that sulfide molecule is produced in high concentration in CRC samples [43]. CRC cell lines treated with PAG (CSE inhibitor) and AOA (CBS inhibitor) lose viability around 60% so that these inhibitors were proposed by some researchers as a solution for inhibition of cancer progression [39,44]. CRC cells treated with NaHS experience a rise in proliferation which is carried out through AKT and ERK phosphorylation and inhibition of tumor suppressor P21 expression [45].…”
Section: Furthermore H2o2 Bolsters the Invasive Behaviors Of Cancer mentioning
confidence: 75%
“…Aged garlic extract (Rodrigues and Percival, 2019) Chemical Burns, treat a plantar wart Allyl disulfide, diallyl disulfide, allicin Garlic paste, crushing garlic (Schimmel et al, 2019) Modern science has identified that garlic contains several health-promoting compounds with therapeutic effects in the area of heart disease and cancer. Recent work points to the existence in garlic of many substances, many of which are organosulfur compounds and bioactive properties (GarcĂ­a and SĂĄnchez-Muniz, 2000;Martins et al, 2016) (Table 2).…”
Section: Sulfurmentioning
confidence: 99%